2016
DOI: 10.1111/pde.12933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiofibromas on Quality of Life and Access to Care in Tuberous Sclerosis Patients and Their Caregivers

Abstract: Presence and lack of treatment of AF significantly impacts QoL in TSC patients and their caregivers. Access to care for AF is limited by multiple factors and should be addressed by clinicians working with this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
(31 reference statements)
3
15
0
Order By: Relevance
“…They reported that the total scores on the DLQI and CDLQI after 12 weeks of treatment did not differ markedly between the sirolimus gel group and the placebo group 7 . Similar ndings were reported in previous studies analyzing the QOL improvement of patients with topical mTOR inhibitors for FA associated with TSC using the DLQI and CDLQI 11,12 . The DLQI and CDLQI are often used for QOL assessments in the treatment of skin diseases 7,13,14 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They reported that the total scores on the DLQI and CDLQI after 12 weeks of treatment did not differ markedly between the sirolimus gel group and the placebo group 7 . Similar ndings were reported in previous studies analyzing the QOL improvement of patients with topical mTOR inhibitors for FA associated with TSC using the DLQI and CDLQI 11,12 . The DLQI and CDLQI are often used for QOL assessments in the treatment of skin diseases 7,13,14 .…”
Section: Discussionsupporting
confidence: 89%
“…FAs in uence the mental status of TSC patients and their families 12 . Since FAs often cause dis gurement, patients personality can become introverted, with reduced sociability 12 . Therefore, the treatment of FA might improve not only skin lesions but also mental health.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the total scores on the DLQI and CDLQI after 12 weeks of treatment did not differ markedly between the sirolimus gel group and the placebo group 7 . Similar findings were reported in previous studies analyzing the QOL improvement of patients with topical mTOR inhibitors for FA associated with TSC using the DLQI and CDLQI 10,11 . The DLQI and CDLQI are often used for QOL assessments in the treatment of skin diseases 7,12,13 .…”
Section: Patient Characteristics Treatment Efficacy and Adverse Eventssupporting
confidence: 89%
“…As regards the proposed algorithm, we believe it is interesting but in our opinion topical rapamycin is always a good first choice and afterwards, if FA are still present (both in children and adults, and in mild but high emotional impact cases), a laser approach is useful, while curettage dermabrasion and electrocoagulation are now outdated. The use of laser therapy for the management of FA in TS has, in fact, been described since 1988 with good response, but long‐term follow‐up suggests high recurrence rates (a mean recurrence time of 3 years) .…”
Section: Discussionmentioning
confidence: 99%